Review of Exchange Arrangements, Restrictions, and Controls. (Policy Papers; Policy Paper ;, 2007)
This review reports on trends, developments, and issues in exchange rate arrangements and currency convertibility. This section presents a summary of the overall findings. Section II provides an overview of key trends and developments in exchange rate arrangements. Section III outlines key trends and developments in current and capital account restrictions. The present paper uses the existing methodology for the classification of exchange rate arrangements.